Shahr-i-Shokhta: Tenth Campaign of the Excavation at the Graveyard - Seyed Sajjadi, Seyed Mansur (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2020)
The 10th excavation campaign in Shahr-i-Shokhta began on Nov 6, 2006 and continued until Jan 5, 2007. In this campaign, excavations followed in different sections of Shahr-i-Sokhta including the cemetery, craftsmen sector, monumental buildings sector, and eastern residential sector. Six out of twelve studied trenches (CMW, HLC, LEI, MIE, NHG, and NKP), each 25 m2 area and a totally 150 m2 were devoid of any cultural material or burial. From the rest, 54 graves were opened that a large number of them, 20 burials, were found inside the NAW trench. The three major structures of the graves included: 33 bipartite, 18 simple pits, 2 catacombs, and an indistinguishable grave. The most valuable finding of this campaign may be an artificial eye found in the cemetery. Preliminary observations on the left eye of a burly woman buried in grave No.6075 have shown that she had an artificial eye made out of bitumen, animal tallow, and golden capillaries.